Evaluating conflict-of-interest governance among Canadian medical societies using a novel assessment tool: A cross-sectional study - Emily Rickard; Joel Lexchin (PLoS ONE, 2026)
Background Medical societies shape clinical standards, develop practice guidelines, and provide continuing education to physicians. Many receive funding from pharmaceutical and medical device companies, creating conflicts of interest (COI); however, organizational-level COI governance in medical societies remains largely unexamined. We developed what is, to our knowledge, the first comprehensive tool to assess medical society COI policies and applied it to Canadian medical societies. Methods and findings We identified 68 Canadian medical societies meeting our inclusion criteria and systematically searched the publicly accessible sections of their websites for COI policies. Two researchers independently analyzed policies using our 51-item tool covering nine domains: continuing medical education/continuing professional development (CME/CPD), leadership COI, clinical practice guidelines, industry relationships, research funding, external funding, annual general meetings, staff COI, and society journals. Only 33 societies (48.5%) had any publicly available COI policy, and those with policies addressed an average of only 1.85 domains (20.5% of possible domain coverage). The most frequently addressed domain was CME/CPD (22 societies, 32.4%), followed by leadership COI (12 societies, 17.6%). Within domains where policies existed, societies covered an average of only 32.5% of relevant items. The most common policy item was speakers’ declaration of COI in CME/CPD activities (16 societies, 23.5%). Policies addressing research funding, external funding, annual meetings, and staff COI were rare (1.5–5.9% of societies). Where present, policies were generally restrictive but narrow in scope. Conclusions Most Canadian medical societies lack comprehensive COI governance, and existing policies are fragmented and reactive. More transparent, comprehensive, and enforceable frameworks are needed to protect institutional independence and public trust. The assessment tool may be adaptable for use in other jurisdictions to support international standardization and best-practice development.